2012
DOI: 10.1089/aid.2011.0295
|View full text |Cite
|
Sign up to set email alerts
|

HIV Type 1 Genetic Diversity in Newly Diagnosed Cuban Patients

Abstract: Knowledge of the genetic diversity of HIV-1 constitutes a fundamental premise in the epidemiological surveillance. In the present study, the HIV-1 genetic variability from 142 Cuban patients who were diagnosed with HIV-1 infection during 2009 and 2010 was determined. HIV-1 subtypes were determined by partial RT-PCR and sequencing of the HIV-1 pol gene. The phylogenetic analysis showed that 47 (33.1 %) samples were subtypes B and 95 (66.9 %) were non-B subtypes, where G, H, and C subtypes, as well as the recomb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 15 publications
2
13
0
6
Order By: Relevance
“…As expected, high genetic diversity was observed, a characteristic that has been previously reported in the Cuban HIV-1 epidemic, probably due to its contacts with Central-Africa [17,19,31] At the FPR cut off set to <20% by G2P tool, we found that 38.1% of patients harbored viruses with reduced susceptibility to use CCR5 co-receptor. Furthermore, the predicted X4 phenotype was detected in 14.3% of the 42 sequences analyzed and associated to the presence of the viral variant CRF19_cpx.…”
Section: Discussionsupporting
confidence: 86%
“…As expected, high genetic diversity was observed, a characteristic that has been previously reported in the Cuban HIV-1 epidemic, probably due to its contacts with Central-Africa [17,19,31] At the FPR cut off set to <20% by G2P tool, we found that 38.1% of patients harbored viruses with reduced susceptibility to use CCR5 co-receptor. Furthermore, the predicted X4 phenotype was detected in 14.3% of the 42 sequences analyzed and associated to the presence of the viral variant CRF19_cpx.…”
Section: Discussionsupporting
confidence: 86%
“…It will be also interesting to trace the origins and global dispersal pathways of those subtype G lineages found in countries outside sub-Saharan Africa, particularly in Cuba [73], [74], [75], Portugal [76], [77], [78], and Russia [79] where this subtype has been disseminated among local populations. It has been showed that the spread of HIV-2 outwards Africa mirrors socio historical ties [80] and a previous study conducted by our group showed that most subtype G Cuban lineages are nested among basal sequences from Central Africa [60].…”
Section: Discussionmentioning
confidence: 99%
“…The subtype B dominates the HIV-1 epidemic in most Caribbean islands [7], [8], [9], [10], [11], [12], [13], [14], with exception of Cuba where several non-B genetic forms are collectively more prevalent [15], [16], [17], [18], [19], [20]. Genetic evidence suggests that the HIV-1 subtype B was introduced from Central Africa into America through Haiti around the middle 1960s, coinciding with the return of many Haitian professionals who worked in the Democratic Republic of Congo [21].…”
Section: Introductionmentioning
confidence: 99%